Historiography does not like haste: Book review: Chachary. A People’s History of Upper Silesia by Dariusz Zalega (Zaranie Śląskie, 2025)
This article is a critical analysis of Dariusz Zalega's book entitled Chachary. Ludowa historia Górnego Śląska (Chachary: A Folk History of Upper Silesia). Although the publication is part of the currently popular trend of folk history and enjoys literary recognition, the reviewer accuses it of a lack of scientific rigour and a journalistic character. The author is criticised for basing his narrative on outdated, communist-era studies, avoiding in-depth archival research and using black-and-white ideological simplifications. As a result, the book is presented not as an objective reconstruction of the past, but as a tool for legitimising contemporary left-wing narratives.
Keywords: folk history; Upper Silesia; historical journalism; historiographical criticism; left wing politics